Logo-Robot “Nodbot” For Correction Of Speech In Preschool Children With Uzbek Language Of Teaching. - Mamurjonovna, Kamolova Yulduzkhon; Mamurjonovich, Kamolov Nodirjon (International Journal of Psychosocial Rehabilitation, 2020)
The article presents one of the possible ways of entertaining the implementation of speech restoration in preschool children with the Uzbek language of instruction using the intellectual robot “NodBot”. Our voice-recognition logo-robot “NodBot” records the voice of children, analyzes speech by comparing it with a previously recorded standard voice and determines the percentage similarity to the amplitude-frequency characteristics of the voice. If the analyzed word coincides with the word from the base in frequency and amplitude by more than 80%, then the logo-robot gives out that the word is spoken correctly, otherwise it suggests listening to the correct version and repeating the word. The proposed method of entertaining speech correction in preschool children with the Uzbek language of instruction using the logo robot can be used by ENT specialists, speech therapists and defectologists in speech therapist kindergartens, in clinics with stationary conditions, as well as parents at home. [1]